1992
DOI: 10.1002/j.1460-2075.1992.tb05381.x
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric ubiquitin conjugating enzyme that combines the cell cycle properties of CDC34 (UBC3) and the DNA repair properties of RAD6 (UBC2): implications for the structure, function and evolution of the E2s.

Abstract: The CDC34 (UBC3) protein from Saccharomyces cerevisiae has a 125 residue tail that contains a polyacidic region flanked on either side by sequences of mixed composition. We show that although a catalytic domain is essential for CDC34 activity, a major cell cycle determinant of this enzyme is found within a 74 residue segment of the tail that does not include the polyacidic stretch or downstream sequences. Transposition of the CDC34 tail onto the catalytic domain of a functionally unrelated E2 such as RAD6 (UBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 32 publications
6
91
0
Order By: Relevance
“…In an elegant experiment the C-terminal (substrate binding) domain was fused to the catalytic domain of yeast UBC2/RAD6. Subsequently it was demonstrated that this hybrid molecule with ubiquitin conjugating activity resulting from the RAD6 portion and substrate recognition conferred by the CDC34 part is able to rescue cdc34 mutants [31,32]. No phenotype has yet been described for the deletion of the yeast UbcH2 homologue UBC8.…”
Section: Resultsmentioning
confidence: 99%
“…In an elegant experiment the C-terminal (substrate binding) domain was fused to the catalytic domain of yeast UBC2/RAD6. Subsequently it was demonstrated that this hybrid molecule with ubiquitin conjugating activity resulting from the RAD6 portion and substrate recognition conferred by the CDC34 part is able to rescue cdc34 mutants [31,32]. No phenotype has yet been described for the deletion of the yeast UbcH2 homologue UBC8.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular functions of only a handful of these extensions are known [38][39][40][41] , and to date, the structural basis for protein-protein interactions mediated by these extensions remain elusive. One of the best understood extensions is in the E2 Ubc2p, which interacts with the E3, Ubr1p.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the structural elements mentioned above, unique parts of some E2s contribute to the specificity of E3 binding as well. For example, the C-terminal tail of a yeast E2 called Cdc34, which is dissimilar to that of a closely related E2 Ubc4, confers specificity of Cdc34 binding to an SCF ligase (Kolman et al 1992;Silver et al 1992). The E3s are the most specific to a given substrate, however.…”
Section: Achieving Specificity Of Ubiquitin Conjugation: Combinatoriamentioning
confidence: 99%